Development and application of a rapid and sensitive genotyping method for pharmacogene variants using the single-stranded tag hybridization chromatographic printed-array strip (STH-PAS). Issue 6 (December 2018) - Kumondai, Masaki; Ito, Akio; Hishinuma, Eiji; Kikuchi, Aoi; Saito, Takahiro; Takahashi, Masamitsu; Tsukada, Chiharu; Saito, Sakae; Yasuda, Jun; Nagasaki, Masao; Minegishi, Naoko; Yamamoto, Masayuki; et al.
Abstract: Genetic polymorphisms contribute to inter-individual variability in the metabolism of multiple clinical drugs, including warfarin, thiopurines, primaquine, and aminoglycosides. A rapid and sensitive clinical assessment of various genome biomarkers is, therefore, required to predict the individual responsiveness of each patient to these drugs. In this study, we developed a novel genotyping method for the detection of nine pharmacogene variants that are important in the prediction of drug efficiency and toxicity. This genotyping method uses competitive allele-specific PCR and a single-stranded tag hybridization chromatographic printed-array strip (STH-PAS) that can unambiguously determine the presence or absence of the gene variant by displaying visible blue lines on the chromatographic printed-array strip. Notably, the results of our STH-PAS method were in 100% agreement with those obtained using standard Sanger sequencing and KASP assay genotyping methods for CYP4F2 gene deletion. Moreover, the results were obtained within 90 min, including the PCR amplification and signal detection processes. The sensitive and rapid nature of this novel method make it ideal for clinical genetic testing to predict drug efficacy and toxicity, and in doing so will aid in the development of individualized medicine and better patient care. Graphical abstract: